Effectiveness of blade tip on low speed horizontal axis wind turbine performance - Ariffudin, Muhammad Hafidz (Penerbit UTM Press, 2016)
There has been an increasing demand for renewable energy in order to create a sustainable society as the non-renewable energies such as fossil fuel resources are limited. Modern wind turbines claim that they have a high efficiency in term of wind energy extraction. However, there are still having losses due to tip vortex causing to a reduction in performance. Motivated by this reason, this research aims at exploring the possibility to increase the performance of low speed small-scaled horizontal axis wind turbine with various tip devices using Computational Fluid Dynamics (CFD). Four wind turbine blades with different tip devices which consist of sword tip, swept tip, upwind winglet and downwind winglet are compared with wind turbine blade without tip device in term of CP. The application of tip device can significantly reduce induced tip vortex and improve wind turbine performance. For TSR below than 4, adding a sword tip increases CP about 7.3%, swept tip increases CP about 9.1%, upwind winglet increases CP about 1.8% and downwind winglet increases CP about 3.2%. It is observed that the best tip device for low wind speed application is swept tip as it give the highest performance increment compared to without tip device.